2019
DOI: 10.1038/s41467-019-11928-w
|View full text |Cite|
|
Sign up to set email alerts
|

Blunting neuroinflammation with resolvin D1 prevents early pathology in a rat model of Parkinson’s disease

Abstract: Neuroinflammation is one of the hallmarks of Parkinson’s disease (PD) and may contribute to midbrain dopamine (DA) neuron degeneration. Recent studies link chronic inflammation with failure to resolve early inflammation, a process operated by specialized pro-resolving mediators, including resolvins. However, the effects of stimulating the resolution of inflammation in PD – to modulate disease progression – still remain unexplored. Here we show that rats overexpressing human α-synuclein (Syn) display altered DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 78 publications
8
121
1
Order By: Relevance
“…In line with the general concepts that bioactive lipid mediators undergo temporal and spatial production during inflammation, that SPMs appear at the peak of acute inflammation in order to later reduce inflammation by activating endogenous resolution programs (7,10) and that chronic inflammation may result from failed resolution mechanisms (12,13), our results display that during the acute phase of the disease (relapsing form) there is an imbalance between pro-inflammatory and proresolving lipid mediators, in favor of the former, and an insufficient or lack of expression of many key SPMs (including E-resolvins, maresins and the rest of Dresolvins), which may in turn affect the outcome of remission and thereby, in theory and yet to be fully elucidated in further studies, even lead to disease progression.…”
Section: Specific Specialized Pro-resolving Mediators Counteract Bloomentioning
confidence: 72%
“…In line with the general concepts that bioactive lipid mediators undergo temporal and spatial production during inflammation, that SPMs appear at the peak of acute inflammation in order to later reduce inflammation by activating endogenous resolution programs (7,10) and that chronic inflammation may result from failed resolution mechanisms (12,13), our results display that during the acute phase of the disease (relapsing form) there is an imbalance between pro-inflammatory and proresolving lipid mediators, in favor of the former, and an insufficient or lack of expression of many key SPMs (including E-resolvins, maresins and the rest of Dresolvins), which may in turn affect the outcome of remission and thereby, in theory and yet to be fully elucidated in further studies, even lead to disease progression.…”
Section: Specific Specialized Pro-resolving Mediators Counteract Bloomentioning
confidence: 72%
“…Different forms of α-Synuclein exhibit distinct effects in triggering microglial phagocytosis and inflammation. Rather than oligomers of α-Synuclein which only induce upregulation of IL-1β (Krashia et al, 2019), fibrillar α-Synuclein is able to elicit strong pro-inflammatory responses in a microglial cell line (Gustot et al, 2015;Hoffmann et al, 2016;Zhou et al, 2016). Fibrillar α-Synuclein can activate NLRP3 inflammasome which leads to the cleaving of pro-inflammatory cytokines, such as IL-1β and IL-18 (Zhou et al, 2016;Chatterjee et al, 2020;Haque et al, 2020).…”
Section: Proteostasis Of α-Synuclein and Inflammation Contribute To Ementioning
confidence: 99%
“…Fibrillar α-Synuclein can activate NLRP3 inflammasome which leads to the cleaving of pro-inflammatory cytokines, such as IL-1β and IL-18 (Zhou et al, 2016;Chatterjee et al, 2020;Haque et al, 2020). Also, using a rat model that overexpresses human α-Synuclein, Krashia et al found that α-Synuclein-induced inflammation precedes nigral degeneration, and administration of resolving D1, a potent lipid mediator that can resolve inflammation to promote restoration of tissue homeostasis, prevents neuronal dysfunction and motor deficits (Krashia et al, 2019). Multiple receptors and pathways are responsible for inducing pro-inflammatory responses in microglia in PD ( Table 1).…”
Section: Proteostasis Of α-Synuclein and Inflammation Contribute To Ementioning
confidence: 99%
“…RvD1 promotes Aβ phagocytosis by macrophages isolated from Alzheimer's patients, reducing the amyloid load [151,152]. Moreover, as cited in Krashia et al, endogenous RvD1 is decreased in patients diagnosed with early-Parkinson's disease [153]. As a result, the decrease of RvD1 levels in Alzheimer's and Parkinson's disease patient's brain could contribute to the disease development and progression.…”
Section: In Humansmentioning
confidence: 93%
“…Moreover, RvD1 induces the polarization of macrophages and microglia toward an M2 phagocytic phenotype [161][162][163]. Chronic and early RvD1 administration in a rat model of Parkinson's disease prevents central and peripheral inflammation, as well as neuronal dysfunction and motor deficits [153]. In addition, the precursors of RvD1, 17R-HDHA and 17S-HDHA, reduce the production of pro-inflammatory cytokines in the spinal cord and in the hippocampus [135,164].…”
Section: In Animalsmentioning
confidence: 99%